Penerapan Terapi Musik Klasik Lullaby Untuk Mengurangi Kecemasan Pada Ibu Hamil Trimester III Di Wilayah Puskesmas Payung Sekaki Kota Pekanbaru - Maswarni; Esti Setiya Wati (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2025)
Classical lullaby music therapy involves slow-tempo tracks with gentle melodies, designed to help reduce anxiety, particularly in third-trimester pregnant women.Research Objective: This study examines the application of classical lullaby music therapy to alleviate anxiety among third-trimester pregnant women in the Puskesmas Payung Sekaki area, Pekanbaru City.Research Method: The study employed a case study approach with two respondents exhibiting varying levels of anxiety.Research Findings: The results demonstrated a significant reduction in anxiety levels and blood pressure for both respondents. Blood pressure shifted from severe to mild and normal categories. Specifically, Respondent 1's anxiety score dropped from 29 (severe) to 10 (mild), while Respondent 2's score decreased from 23 (severe) to 10 (mild).Conclusion: Regular use of classical lullaby music therapy proved effective in lowering anxiety levels in third-trimester pregnant women, offering a practical self-administered option for patients